Controls on surface water quality in the River Clyde catchment, Scotland, UK, with particular reference to chromium and lead. (13th November 2018) - Bearcock, J. M.; Smedley, P. L.; Fordyce, F. M.; Everett, P. A.; Ander, E. L.
ABSTRACT: Three collated geochemical surveys of surface water in the Clyde catchment have established the spatial variability in water composition, primarily under baseflow conditions. The waters are broadly pH-neutral to alkaline (maximum pH 8.7) in the lowlands, but mildly acidic in uplands on the catchment periphery. Electrical conductance is relatively high in lowland streams (maximum 8320μgL –1 ), with lower values in the uplands. Dissolved chromium (Cr; <0.05–971μgL –1 ) and lead (Pb; <0.05–19.4μgL –1 ) are of importance due to recognised pollution sources within the catchment. High aqueous Cr concentrations (>5μgL –1 ) are recorded in urban areas associated with the disposal of alkaline industrial chromite ore processing residue. Under such conditions, Cr probably occurs as Cr(VI). Numerous relatively high Pb values occur in the upland and urban areas. These are likely to be associated with a combination of soil reactions, diffuse pollution and contamination from Pb mineralisation/mining. Pb has a stronger correlation with water pH than with stream sediment Pb content, suggesting that pH has a greater control on Pb mobility than host-rock Pb. Exceedances of water-quality standards are <1% for both Cr and Pb across the catchment. Absolute exceedances are more extreme for Cr than for Pb, highlighting the scale of the Cr pollution problem for urban surface water within the catchment.